The Shift in the Legal Politics of Regulating the General Principles of Good Governance in Indonesian Legislation - Fauzani, Muhammad Addi (As-Siyasi: Journal of Constitutional Law, 2023)
This article aims to analyze the shift in the form of legal politics in implementing the General Principles of Good Governance (AUPB) in Indonesia, including its legal consequences. With the explicit mention of AUPB in the new Law on Government Administration, this becomes an interesting topic from a legal and political perspective. Before the enactment of Law Number 30 of 2014 concerning Government Administration, the regulation of the General Principles of Good Governance (AUPB) was still abstract and unclear in its direction and implementation. This research is a normative juridical research using a statutory approach. The findings of this research reveal that the shift in the legal politics of AUPB in Indonesia through Law Number 30 of 2014 concerning Government Administration has shifted the format of legal politics in Indonesia. This shift has had a positive influence on the development of legal politics in Indonesia, including: a) making the status of principles into concrete legal norms; b) making it easier for the courts to adjudicate an action by administrative officials; c) facilitating control of administrative actions; d) simplifying public control; e) emphasizing the importance of supervision of official actions; f) guarantee civil rights; g) prevent government arbitrariness against civilians